The Protective Role of Magnesium Sulphate on Steroid Induced Liver Damage in Albino Rats (Medical Forum Monthly, 2024)
Objective: Dexamethasone causes metabolic disorders and morphological adverse effects on several organs of the body such as testes, kidney, bone, eye and liver etc. Most commonly it causes damage to liver morphology and its functions. Magnesium is an essential mineral of the body, currently is a subject of interest in medicine. Therefore the present study was designed to observe the ameliorating role of magnesium on dexamethasone induced liver damage and correlate the result with previous studies.Study Design: Experimental StudyPlace and Duration of Study: This study was conducted in the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi, from 21 April to 10 May 2012.Materials and Methods: Thirty adult albino rats, weighing from 200-300 grams were taken for this study. The rats were divided into 3 groups, Group A served as control , Group B received inj. dexamethasone 4mg/kg and Group C received inj. dexamethasone 4mg/kg with inj. Magnesium sulphate(MgSO4) 20mg/kg for 20days at the end of which they were sacrificed and liver tissue sections stained with haematoxylin and eosin.Results: There was marked decrease in weight observed in rats receiving dexamethasone. Haematoxylin and eosin stained sections showed dilated central vein and sinusoids. Moderate fatty infiltration showed in vacuolated hepatocytes with absent or distorted nuclei in dexamethasone group which were protected and reverted to a major extent in Magnesium sulphate along with dexamethasone receiving group.Conclusion: This study has proved that use of Magnesium sulphate along with dexamethasone ameliorates dexamethasone induced damaging effects on liver.